2006
DOI: 10.55095/achot2006/046
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Fracture of the Ring of Axis - "Hangman's Fracture"

Abstract: PURPOSE OF THE STUDYTo evaluate surgical management of the fracture of the ring of axis (FRA), known as "hangman's fracture", and to discuss adequacy of this treatment. MATERIAL AND METHODSBetween 1994 and 2004, 41 patients with FRA were surgically treated in our hospital. We present a retrospective study of 30 cases treated by anterior cervical fixation and fusion and 11 cases treated by a posterior, CT-guided approach (published recently).Our diagnostic algorithm for evaluation of FRA included plain radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Suchomel et al 13 reported that oblique compression load is the main mechanism of type II odontoid fracture, over-extension is the main mechanism of the anterior and posterior arch of atlas fractures, axial compression load is the main mechanism of atlas burst fracture, and compression combined with lateral flexion is the main mechanism of unilateral atlas lateral mass. Therefore, it is crucial for the physician to select the appropriate treatment for UCS complex fractures, taking into consideration the patient’s characteristics and injury pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Suchomel et al 13 reported that oblique compression load is the main mechanism of type II odontoid fracture, over-extension is the main mechanism of the anterior and posterior arch of atlas fractures, axial compression load is the main mechanism of atlas burst fracture, and compression combined with lateral flexion is the main mechanism of unilateral atlas lateral mass. Therefore, it is crucial for the physician to select the appropriate treatment for UCS complex fractures, taking into consideration the patient’s characteristics and injury pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Z hlediska etiologie panuje mezi autory včetně naší práce jednoznačná shoda, že k poranění dochází nejčastěji po pádech z výše stojícího člověka, tedy nízkoenergetickým násilím (11,18,20,22,23). Typickým znamením hyperextenzního poranění je exkoriace na hlavě, nejčastěji v oblasti čela (1,3,23,25). Dalším častým nálezem u pacientů poraněných při pádu je ebrieta (3,22).…”
Section: Výsledkyunclassified